2022
DOI: 10.1177/20552076221129069
|View full text |Cite
|
Sign up to set email alerts
|

Internet-facilitated interventions for informal caregivers of patients with neurodegenerative disorders: Systematic review and meta-analysis

Abstract: Objective This systematic review explored the effectiveness of internet-delivered interventions in improving psychological outcomes of informal caregivers for neurodegenerative-disorder (ND) patients. Methods We searched seven databases for English-language papers published from 1999 to May 2021. Study-eligibility required that interventions used a minimum 50% internet-facilitation, targeting unpaid, adult informal caregivers of community-based ND-patients. We included randomised controlled trials (RCTs) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 130 publications
1
1
0
Order By: Relevance
“…Leng and collaborators highlighted how the online support interventions examined signi cantly improved depressive symptoms, perceived stress, anxiety, and caregivers' self-e cacy, while no signi cant improvements were found in caregiver burden, ability to cope with behavioral symptoms or quality of life [38]. The results are in line with a recent study where participants in online interventions showed a signi cant improvement in caregiving ability and anxiety compared to control groups; modest results were also noted in measures of quality of life and caregiver burden [33].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Leng and collaborators highlighted how the online support interventions examined signi cantly improved depressive symptoms, perceived stress, anxiety, and caregivers' self-e cacy, while no signi cant improvements were found in caregiver burden, ability to cope with behavioral symptoms or quality of life [38]. The results are in line with a recent study where participants in online interventions showed a signi cant improvement in caregiving ability and anxiety compared to control groups; modest results were also noted in measures of quality of life and caregiver burden [33].…”
Section: Discussionsupporting
confidence: 81%
“…In general, recent ndings concur in a rming that the online intervention mode is acceptable, feasible, and promotes health and well-being bene ts for caregivers, especially in self-e cacy, anxiety, and depression measures [30,31]. They also highlight heterogeneity in experimental designs, populations, and outcome measurement, making it challenging to identify parameters that guarantee the effectiveness of such interventions [32,33].…”
mentioning
confidence: 93%